Transfusion-Transmitted Malaria: Two Pediatric Cases From the United States and Their Relevance in an Increasingly Globalized World. (24th September 2021) - Stubbs, Leigh A; Price, Michael; Noland, Daniel; Fuchs, Jennifer; Filkins, Laura; McElvania, Erin; Luu, Hung S; Sebert, Michael; Waters, Ami; Hsiang, Michelle S
Abstract: In non-endemic settings, transfusion-transmitted malaria (TTM) is rare but potentially fatal and becoming more common with globalization. We present two pediatric cases that demonstrate donor screening using questionnaires is subject to error and that TTM should be considered with fever following numerous transfusions in children, particularly sickle cell patients.